Effects of different sex ratios on the growth and ovarian development of the ridgetail white shrimp, Exopalaemon carinicauda - Zhiyu Pang; Zhenhui Zhao; Yongchuang Li; Yuqi Sun; Chun Duan; Binlun Yan; Wazir Ali Baloch; Qingyu Zhou; Huan Gao (Aquaculture Reports, 2022)
To study the effects of sex ratio differences on the growth and ovarian development of Exopalaemon carinicauda, and their mechanism, we cultured female shrimps with different numbers of males for five weeks, and measured the growth and ovarian development index of relevant individuals. The results show that: 1) the existence of males reduced the growth rate of females, but significantly improved the ovarian development rate of female individuals. The growth rate of females living with the same sex was significantly accelerated, but their ovarian development rates were relatively slow. 2) Four kinds of communication modes between females and males were tested; i.e., free contact, chemical signals, visual signals, and coexisting chemical and visual signals. Of these four types, free contact improved the ovarian development of females. Under the condition of free contact, the period of the ovarian development cycle was shortened, more nutrients accumulated in the ovary, the amount of sex hormones and Vitellogenin (Vg) increased, and the expression of the gonad-inhibitory hormone (gih) gene tended to decrease. We speculated that testosterone released by males may play an important role in these phenomena. 3) Although the different sex ratios had no significant effect on the growth of females, the speed of ovarian development significantly increased when the female: male ratio was 1:2.